Steric Impediment of Ion Migration Contributes to Improved Operational Stability of Perovskite Solar Cells - YAVUZ, İLHAN (WILEY-V C H VERLAG GMBH, 2020)
The operational instability of perovskite solar cells (PSCs) is known to mainly originate from the migration of ionic species (or charged defects) under a potential gradient. Compositional engineering of the A site cation of the ABX(3) perovskite structure has been shown to be an effective route to improve the stability of PSCs. Here, the effect of size-mismatch-induced lattice distortions on the ion migration energetics and operational stability of PSCs is investigated. It is observed that the size mismatch of the mixed A site composition films and devices leads to a steric effect to impede the migration pathways of ions to increase the activation energy of ion migration, which is demonstrated through multiple theoretical and experimental evidence. Consequently, the mixed composition devices exhibit significantly improved thermal stability under continuous heating at 85 degrees C and operational stability under continuous 1 sun illumination, with an extrapolated lifetime of 2011 h, compared to the 222 h of the reference device.
Keywords: acetamidinium; ion migration; perovskite solar cells; stability; steric engineering; TOTAL-ENERGY CALCULATIONS; LEAD IODIDE; HALIDE PEROVSKITES; EFFICIENT; DEGRADATION; PERFORMANCE; METHYLAMMONIUM; FORMAMIDINIUM; SUBSTITUTION; STATE